1997
DOI: 10.1002/(sici)1098-2396(199702)25:2<147::aid-syn5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

p-[18F]-MPPF: A potential radioligand for PET studies of 5-HT1A receptors in humans

Abstract: The purpose of this study was to develop a radiopharmaceutical that could be used to selectively image 5-HT1A receptors with positron emission tomography (PET). No-carrier-added 4-(2'-methoxyphenyl)-1-[2'-(N-2"-pyridinyl)-p-[18F] fluorobenzamido]ethylpiperazine (p-[18F]-MPPF, 2) was synthesized by the nucleophilic substitution of the corresponding nitro precursor 1 with K[18F]/Kryptofix 2.2.2. in dimethyl sulfoxide (DMSO) at 140 degrees C for 20 min followed by purification with high-performance liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 33 publications
4
59
0
Order By: Relevance
“…Preadministration of a high dose of 8-OH-DPAT blocks [ 11 C]WAY-100635 specific uptake in the frontal cortex substantially (Farde et al, 1997;Mathis et al, 1994). Administered during a PET scan, 8-OH-DPAT displaces [ 11 C]WAY-100635 (Mathis et al, 1994;Tsukada et al, 2001) and [ 18 F]MPPF (Shiue et al, 1997). In ex vivo studies in rats, 8-OH-DPAT blocks the binding of H]WAY-100635 (Hume et al, 1994), [ 11 C]WAY-100635 (Mathis et al, 1994) and [ 18 F]MPPF (Shiue et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preadministration of a high dose of 8-OH-DPAT blocks [ 11 C]WAY-100635 specific uptake in the frontal cortex substantially (Farde et al, 1997;Mathis et al, 1994). Administered during a PET scan, 8-OH-DPAT displaces [ 11 C]WAY-100635 (Mathis et al, 1994;Tsukada et al, 2001) and [ 18 F]MPPF (Shiue et al, 1997). In ex vivo studies in rats, 8-OH-DPAT blocks the binding of H]WAY-100635 (Hume et al, 1994), [ 11 C]WAY-100635 (Mathis et al, 1994) and [ 18 F]MPPF (Shiue et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Administered during a PET scan, 8-OH-DPAT displaces [ 11 C]WAY-100635 (Mathis et al, 1994;Tsukada et al, 2001) and [ 18 F]MPPF (Shiue et al, 1997). In ex vivo studies in rats, 8-OH-DPAT blocks the binding of H]WAY-100635 (Hume et al, 1994), [ 11 C]WAY-100635 (Mathis et al, 1994) and [ 18 F]MPPF (Shiue et al, 1997). Buspirone and ipsapirone at doses of 2 mg/kg blocked B50% of [O-methyl-3 H]WAY-100635 specific binding in all regions examined in an ex vivo study in rats, while 5 mg/kg buspirone occupied 61% of frontal cortex 5-HT 1A receptor in an [ 11 C]WAY-100635 PET study using a monkey (Farde et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Animal Care Committee of the University of Groningen. Shiue et al (1997) for a comparable method). It was formulated into a 5% NaCl solution.…”
Section: Animalsmentioning
confidence: 99%
“…This time point is based on earlier studies which showed that 30 min after injection, MPPF binding reaches a state of transient equilibrium (Plenevaux et al, 2000b;Shiue et al, 1997). The brains were removed from the skull, frozen in isopentane (À801C), cut into 80 mm coronal slices in a cryostat at -101C, thaw mounted onto glass slides, exposed to a phosphor storage screen (Packard) for at least 10 halflife times (18-20 h) and scanned using the Cyclone storage phosphor system.…”
Section: Ex Vivo Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation